Historical background of current surgical management of paediatric ovarian masses. - Michalik-Jarczyńska, Karolina; Sosnowska-Sienkiewicz, Patrycja; Mańkowski, Przemysław (Medicina Historica, 2025)
Ovarian masses are rare in paediatric population and surgery remains one of the key elements of treatment. Approaches to the operative management of ovarian lesions in children and adolescents changed over decades with the development of diagnostic imaging – especially ultrasonography and minimally-invasive surgical techniques. The aim of this study is to examine research focused on the history of diagnostic and surgical procedures, and to present the historical background of the current management of ovarian masses in children and adolescents. It describes the development of particular diagnostic and surgical techniques, how this evolution contributed to improvements in treatment and how it led to the current state of art. The article constitutes a literature review and mainly focuses on medical inventions between the 18th and 21st centuries, but it also mentions important issues from earlier periods.